Spatiotemporal Water Quality Assessment of Lake Mahalona via Google Earth Engine - Asramid Yasin; Muhammad Saleh Qadri; Herlan Hidayat; Nayla Desviona (Gema Lingkungan Kesehatan, 2026)
Freshwater lake ecosystems are increasingly recognized as sensitive indicators of environmental health, where shifts in physicochemical water quality parameters reflect broader ecological pressures from anthropogenic activities and climate variability This study aims to map the spatial distribution, analyze temporal trends, and evaluate the water quality status of Lake Mahalona in Towuti Subdistrict, East Luwu Regency, South Sulawesi, based on pH, TSS, BOD, COD, and ammonia parameters. The analysis was conducted using the GEE platform with Sentinel 2 Level-2A imagery data for pH, TSS, BOD, and COD parameters, as well as GEOS-CF data for ammonia, covering the period from January to November 2025. The methods applied included creating an Area of Interest (AOI), using the JRC Global Surface Water Mapping Layers, v1.4, utilizing Harmonized Sentinel-2 MSI Level-2A (SR), atmospheric correction, cloud and water body masking, outlier removal using the inter-quantile range, deriving functional equations for water quality parameters, and exporting the data. Satellite-derived estimates yielded pH values ranging from 6.587 to 7.154; TSS from 17.55 to 19.821 mg/L; BOD from 3.215 to 7.266 mg/L; COD from 2.857 to 6.116 mg/L; and atmospheric ammonia pressure indicators at 0.001 mg/L. Time-series analysis revealed fluctuations in all parameters, with increases in TSS, BOD, and COD from August to October, while ammonia remained stable at very low concentrations. Based on Government Regulation No. 22 of 2021, the pH, TSS, COD, and ammonia parameters still meet Class II and III water quality standards; however, the BOD value has exceeded the 2 mg/L threshold, indicating organic pollution pressure from anthropogenic activities in the watershed. The GEE-based approach demonstrates considerable potential for efficient spatial and temporal monitoring of lake water quality, providing important baseline information for the sustainable management and conservation of Lake Mahalona.